Social Media Strategy Development: A Case Study in Serial Petualangan si Unyil 3D Animation - Ismanto, Abdullah Fikri; Fachira, Ira (Journal of Business and Management, 2016)
Abstract. The purpose of this study is to develop Social media strategy as a part part of promotion initiatives for Serial Petualangan Si Unyil. A market research was conducted to explore womenâ€™s social media preference and usage pattern in Bandung and Jakarta. A survey was distributed to 400 respondents targeted by PFN: women who has kids aged 3 to 12 years old. Findings show that Facebook, Path, and Instagram as the most used social networking media (43.7 %, 42% and 38.5 % respectively). The most popular social media messaging is Whatsapp which is chosen by 74% respondents. A social media strategy was developed using Gilfoil, Aukers & Jobsâ€™ (2015) framework comprising defining social media goals, developing social media strategy and designing a tactical plan.Â Keywords: Social Media, Promotion Strategy, Television Program, Animation